The Prisoner’s Right to Receive Cross-Border Health Care Services - Milašiūtė, Vygantė (Teisė, 2018)
The article from a human rights perspective examines whether persons serving a sentence of deprivation of liberty in Lithuania have a right to avail themselves of the freedom of movement seeking to receive health care services in another EU Member State. Analysis is based on legal acts of the Republic of Lithuania and the EU as well as the ECHR.
Keywords: none